ABCB5+ mesenchymal stromal cells therapy protects from hypoxia by restoring Ca2+ homeostasis in vitro and in vivo - Yan, Kaixuan; Zheng, Jiaxing; Kluth, Mark Andreas; Li, Lin; Ganss, Christoph; Yard, Benito A.; Magdeburg, Richard; Frank, Markus H.; Pallavi, Prama; Keese, Michael (Stem cell research & therapy, 2023)
Hypoxia in ischemic disease impairs Ca2+ homeostasis and may promote angiogenesis. The therapeutic efficacy of mesenchymal stromal cells (MSCs) in peripheral arterial occlusive disease is well established, yet its influence on cellular Ca2+ homeostasis remains to be elucidated. We addressed the influence of ATP-binding cassette subfamily B member 5 positive mesenchymal stromal cells (ABCB5+ MSCs) on Ca2+ homeostasis in hypoxic human umbilical vein endothelial cells (HUVECs) in vitro and in vivo. Hypoxia was induced in HUVECs by Cobalt (II) chloride (CoCl2) or Deferoxamine (DFO). Dynamic changes in the cytosolic- and endoplasmic reticulum (ER) Ca2+ and changes in reactive oxygen species were assessed by appropriate fluorescence-based sensors. Metabolic activity, cell migration, and tube formation were assessed by standard assays. Acute-on-chronic ischemia in Apolipoprotein E knock-out (ApoE−/−) mice was performed by double ligation of the right femoral artery (DFLA). ABCB5+ MSC cells were injected into the ischemic limb. Functional recovery after DFLA and histology of gastrocnemius and aorta were assessed. Hypoxia-induced impairment of cytosolic and ER Ca2+ were restored by ABCB5+ MSCs or their conditioned medium. Similar was found for changes in intracellular ROS production, metabolic activity, migratory ability and tube formation. The restoration was paralleled by an increased expression of the Ca2+ transporter Sarco-/endoplasmic reticulum ATPase 2a (SERCA2a) and the phosphorylation of Phospholamban (PLN). In acute-on-chronic ischemia, ABCB5+ MSCs treated mice showed a higher microvascular density, increased SERCA2a expression and PLN phosphorylation relative to untreated controls. ABCB5+ MSCs therapy can restore cellular Ca2+ homeostasis, which may beneficially affect the angiogenic function of endothelial cells under hypoxia in vitro and in vivo.
Im Titel sind + und 2+ hochgestellt
Gesehen am 14.10.2024